The Association of Single Nucleotide Polymorphism -69T>G HSPA1A Gene with Bali Cattle Heat Tolerance - I. Suhendro; J. Jakaria; R. Priyanto; W. Manalu; R. R. Noor (Faculty of Animal Science, Bogor Agricultural University, 2022)
Heat shock protein plays an essential role in thermoregulatory during heat stress responses. This study aims to determine the association of single nucleotide polymorphism (SNP) -69T>G in the promoter region of the heat shock protein 70 member 1A (HSPA1A) gene on heat tolerance in Bali cattle. One hundred and sixteen heads of Bali cattle were collected from different locations such as Pangyangan, Bali Island; Serading, Sumbawa Island; and Sembalun, Lombok Island. The SNP was analyzed by genotyping using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), which used BstUI enzyme restriction. Physiological responses including respiration rate (Rr), rectal temperature (Tr), heart rate (Hr), heat tolerance coefficient (HTC), and blood glucose level (Glu) were measured. Association analysis was conducted using a general linear model by setting genotype, altitude, and sex as factors. The SNP -69T>G variant of HSPA1A gene found in this study were wild type (TT) with 144 bp & 498 bp; GG with 144, 236, & 262 bp; and TG with 144, 236, 262, & 498 bp. Bali cattle with the GG genotype had lower (p<0.001) Rr and HTC compared to the other genotypes. It could be concluded that physiological performances were lower at high altitudes, and the SNP -69T>G HSPA1A was associated with the physiological performances of Bali cattle. SNP -69T>G of HSPA1A could be utilized for candidate marker-assisted selection of Bali cattle to improve the performance of heat tolerance.